Testing the Rational Expectations Hypothesis on the Retail Trade Sector Using Survey Data from Malaysia - Puah, Chin Hong; Lee, Lucy Yun Chong; Mohamad, Jais (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The rational expectations hypothesis states that when people are expecting things to happen, using the available information, the predicted outcomes usually occur. This study utilized survey data provided by the Business Expectations Survey of Limited Companies to test whether forecasts of the Malaysian retail sector, based on gross revenue and capital expenditures, are rational. The empirical evidence illustrates that the decision-makers expectations in the retail sector are biased and too optimistic in forecasting gross revenue and capital expenditures.